Characterization of properties and deterioration by termites in the Pinus elliottii Engelm. wood - Gallio, Ezequiel; Costa, Henrique Weber Dalla; Guerreiro, Laíse; Cruz, Nidria Dias; Beltrame, Rafael; Gatto, Darci Alberto (Scientia Agraria Paranaensis, 2020)
The technological properties of wood are constituted by parameters, which after being analyzed, make it possible to define an appropriate use for this material. However, the deterioration of the wood due to the attack of termites, which find their food source in the chemical components, ends up altering these original technological characteristics, reducing their useful life and compromising their use. Thus, this study aimed to determine some technological properties of Pinus elliottii, as well as to evaluate the influence of deterioration caused by Nasutitermes termites in this wood. Specimens with dimensions of 20 x 20 x 150 mm (tangential x radial x longitudinal) were used as specimens. The physical properties evaluated were the basic density and linear shrinkage (tangential and radial contractions, and anisotropy coefficient), while the mechanical properties were represented through the Janka hardness test and compression parallel to the fibers. After 40 days of the biodeterioration test with Nasutitermes termites, changes in the equilibrium moisture content, retractability, water absorption rate and mechanical properties were evaluated. While the physical and mechanical properties evaluated showed values similar to those found in the literature, the deterioration caused by termites caused a reduction in hardness and parameters related to compression, increasing the dimensional instability of the wood, represented by the variation in the anisotropy coefficient. This made it possible to conclude that the biodeterioration resulting from the attack of termites directly affected the technological parameters of the wood, and consequently, its quality for the use in the purpose it could initially be destined.